Complexity and approximability of scheduling resumable proportionally deteriorating jobs - Gawiejnowicz, Stanisław; Kononov, Alexander (European journal of operational research, 2010)
A set of independent, resumable and proportionally deteriorating jobs is to be executed on a single machine. The machine is not continuously available for processing but the number of non-availability periods, the start time and end time of each period are known in advance. The criterion of schedule optimality is the maximum completion time. It is proved that the decision version of the problem with a single non-availability period is ordinarily NP -complete. It is also proved that for the problem with a single non-availability period there exists a fully polynomial-time approximation scheme. Finally, it is proved that for the problem with two or more non-availability periods there does not exist a polynomial-time approximation algorithm with a constant worst-case ratio, unless P = NP .